1998
DOI: 10.1080/14427591.1998.9686436
|View full text |Cite
|
Sign up to set email alerts
|

Occupation as a mediator of depression in people with rheumatoid arthritis

Abstract: In this study we investigate the association between rheumatoid arthritis and depression, and examine if the increase in depression among individuals with rheumatoid arthritis (RA) compared to individuals without RA, is attributable to poor ability to perform important daily occupations. The occupations of work, self care, leisure, rest and sleep were analysed, using regression analyses, to see which predicted depression. The participants were 143 adults with rheumatoid arthritis (RA) and 142 without RA. A dai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…Evidence suggesting that individuals with RA experienced occupational limitation is overwhelming (Blalock, Orlando, Mutran, DeVellis & DeVeillis, 1998;Giorgino et al;Katz & Yelin 1994a;MacKinnon, Noh, & Miller, 1998;MacKinnon, 1992;Yelin, Lubeck, Holman, & Epstein, 1998). Furthermore, there is evidence to suggest a strong link between occupational performance and certain aspects of psychological well-being.…”
Section: The Role Of Occupationmentioning
confidence: 99%
See 1 more Smart Citation
“…Evidence suggesting that individuals with RA experienced occupational limitation is overwhelming (Blalock, Orlando, Mutran, DeVellis & DeVeillis, 1998;Giorgino et al;Katz & Yelin 1994a;MacKinnon, Noh, & Miller, 1998;MacKinnon, 1992;Yelin, Lubeck, Holman, & Epstein, 1998). Furthermore, there is evidence to suggest a strong link between occupational performance and certain aspects of psychological well-being.…”
Section: The Role Of Occupationmentioning
confidence: 99%
“…Considerable research attention has focused on the nature and consequences of this chronic illness, with a growing body of literature investigating the psychological well-being of individuals who have RA. To date studies have shown that individuals with RA have higher levels of depression and anxiety (Krol et al, 1993;MacKinnon, Noh, & Miller, 1998;Smedstad, Moum, Vaglum, & Kvien, 1996), both of which were linked with chronic illness in general (Fitzpatrick, Newman, Lamb, & Shipley, 1988;Katz & Yelin, 1994b;Sheasby, Barlow, Cullen, & Wright, 2000) and loss of engagement in valued occupations (Katz & Yelin, 1994a). Evidence examining the presence, level, and consequence of self-esteem has received less attention, especially when considering important aspects of occupational limitations experienced and the impact on the individual living with a chronic illness.…”
mentioning
confidence: 99%
“…‘Arthritis is one of the most prevalent chronic health conditions and also the leading cause of physical disability in non‐institutionalised adult populations’ (MacKinnon, Noh & Miller, 1998; p. 82). A health needs study by the North Eastern Health Care Network (1997), of which the ARMC was a part, stated that this clinical group was the most prevalent disabling condition for all age groups over 25 years of age, in the geographical locality.…”
Section: Introductionmentioning
confidence: 99%
“…(1999) demonstrated that pain levels, physical disability, psychological distress and disease severity can predict the concerns and learning needs of this client group. Furthermore, MacKinnon et al (1998) stated that depression in people with rheumatoid arthritis is associated with the ‘severity or degree of disability, functional loss, pain and occupational deprivation’ (p. 83).…”
Section: Introductionmentioning
confidence: 99%
“…The stress resulting from the inability to perform simple day to day tasks independently, the associated discomfort and the insult to patient’s aesthetic sensibilities result in high levels of depression in this group; at approximately 20% it is twice that of the general population [ 4 ]. It is well recognised that occupation, including paid employment has a large influence on personal well being and society as a whole [ 5 - 8 ].…”
mentioning
confidence: 99%